2001
DOI: 10.1080/028418501127347340
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of the MR contrast agent MnDPDP and its metabolite MnPLED upon reperfusion of the ischemic porcine myocardium

Abstract: MnPLED seems to reduce reperfusion-induced cardiac dysfunction and infarct size in pigs. MnDPDP does not reduce infarct size in the pig, probably because of the rapid exchange of Mn2+ for Zn2+ taking place in the pig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Manganese ions need to be dissociated from their ligand in order to be taken up by the myocardial cells (13). In pigs the main mechanism for dissociating Mn 2ϩ -ions from Mn-DPDP is transmetallation of the Mn 2ϩ -ions for Zn 2ϩ in the DPDP molecule, while in, for example, humans and rats a large part of the Mn-DPDP is instead metabolized in the liver into manganese dipyroxidyl diamine (Mn-PLED) (17,20,21). Because of this, the intracellular contrast effect of Mn-DPDP is limited by the amount of Zn 2ϩ -ions in the blood and the speed at which the transmetallation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Manganese ions need to be dissociated from their ligand in order to be taken up by the myocardial cells (13). In pigs the main mechanism for dissociating Mn 2ϩ -ions from Mn-DPDP is transmetallation of the Mn 2ϩ -ions for Zn 2ϩ in the DPDP molecule, while in, for example, humans and rats a large part of the Mn-DPDP is instead metabolized in the liver into manganese dipyroxidyl diamine (Mn-PLED) (17,20,21). Because of this, the intracellular contrast effect of Mn-DPDP is limited by the amount of Zn 2ϩ -ions in the blood and the speed at which the transmetallation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent experimental studies in pigs revealed that the metabolite from Mn-DPDP namely manganese dipyridoxyl ethyldiamine (MnPLED) could reduce postischemic reperfusion-induced cardiac dysfunction and infarct size (Karlsson et al 2001). Therefore, the use of a Mn 2+ -releasing contrast agents such as Mn-DPDP may be a promising multipurpose approach.…”
Section: Intracellular Contrast Agentsmentioning
confidence: 98%
“…Similar approach has been adopted in cardiac MRI using cold cation Mn 2+ preparations as intracellular contrast agents for infarct imaging, since Mn 2+ is potent for T1 shortening and is taken up only in cells capable of active calcium (Ca 2+ ) transport, and thereby provides an analog to 201 Tl imaging in cardiac scintigraphy (Bremerich et al 2000;Karlsson et al 2001;Flacke et al 2003;Storey et al 2003;Krombach et al 2004). Mn 2+ has an ionic radius similar to that of Ca 2+ and is known to enter myocytes via voltage-facilitated calcium channels.…”
Section: Intracellular Contrast Agentsmentioning
confidence: 98%
“…Correspondingly, in this study, we found that MnPLED and Dp-dp significantly decreased 7β-OH-induced ROS production. SOD mimetic activity of MnPLED [11] may account for this decline in ROS production in cells exposed to 7β-OH. We tested this hypothesis by measuring the levels of MnSOD in cells exposed to MnPLED and Dp-dp.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that a metabolite of mangafodipir, MnPLED, possesses SOD-like activity and has potential to reduce oxidative injuries in the heart [11]. Additionally, fodipir (Dp-dp) has a metal ion-chelating effect, which also might contribute to the anti-oxidant property.…”
Section: Introductionmentioning
confidence: 99%